Human capital’s dual impact: Advancing innovation and technology diffusion in ASEAN-5 through the Nelson-Phelps-Romer Lens - Nguyen Ngoc Thach (PLoS ONE, 2025)
The advanced ASEAN nations—Indonesia, Malaysia, the Philippines, Singapore, and Thailand—are navigating significant global uncertainties that challenge their industrialization ambitions. Human capital, recognized as a pivotal driver of technological progress, has not been adequately integrated into growth models for these countries. This study investigates the dual function of human capital within an extended Nelson-Phelps framework of technology diffusion, incorporating Romer’s insights, across these five ASEAN countries from 1965 to 2019. Employing a Bayesian hierarchical analysis with specific informative priors effectively addresses statistical challenges. The findings reveal that human capital accelerates both domestic innovation and the adoption of foreign technologies in these nations. Notably, high-skilled labor significantly contributes to technological advancements, and domestic innovation plays a more substantial role in enhancing productivity growth than technology imitation. The extended Nelson-Phelps framework, which incorporates human capital’s role in both innovation and technology diffusion, is well-suited for modeling the catch-up development of ASEAN economies. These insights offer valuable contributions to growth literature and practical applications in technology catch-up strategies.